Mechanisms of Environmental-Induced Autoimmunity - Pollard, K. Michael (Annu Rev Pharmacol Toxicol, 2020)
Although numerous environmental exposures have been suggested as triggers for pre-clinical autoimmunity, only a few have been confidently linked to autoimmune diseases. For disease associated exposures, the lung is a common site where chronic exposure results in cellular toxicity, tissue damage, inflammation, and fibrosis. These features are exacerbated by exposures to particulate material, which hampers clearance and degradation thus facilitating persistent inflammation. Coincident with exposure and resulting pathological processes is the post-translational modification of self-antigens, which, in concert with the formation of tertiary lymphoid structures containing abundant B cells, is thought to promote the generation of autoantibodies that in some instances demonstrate major histocompatibility complex restriction. Under appropriate gene-environment interactions these responses can have diagnostic specificity. Greater insight into the molecular and cellular requirements governing this process, especially those that distinguish pre-clinical autoimmunity from clinical autoimmune disease, may facilitate determination of the significance of environmental exposures in human autoimmune disease.